ANALYSIS CHEMICAL COMPOSITION OF SEA URCHIN SHELL (Diadema setosum) - yusri munthe; Mirna Ilza; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2023)
ABSTRACT Diadema setosum or sea urchin is a marine biota that has high economic value. This study aims to determine the chemical composition of sea urchin shells. This research phase consisted of flouring sea urchin shells and the observations made were chemical composition tests. The results of this study indicate that the sea urchin shell has a chemical composition such as a moisture content of 1.47 ± 0.42%, an ash content of 82.31 ± 1.10%, a fat content of 1.15 ± 0.19% and a protein content of 6.84 ± 0.26%.